Sense of place: Chew Jetty in George Town historical city, Penang - Ismail, Sumarni; Tan, Kuan Meng; Yusoff, Sarizal Yusman; Utaberta, Nangkula; Mohd Yunus, Mohd. Yazid; Ismail, Nor Atiah (American-Eurasian Network for Scientific Information, 2015)
This paper is to identify the elements of sense of place at Chew Jetty and to identify which is the most important element of sense of place that creating the uniqueness of Jetty. Sense of place is a primary concern in urban design, as it determines whether a place is sensitive towards its context. This, assessment was done through perceptual survey, behavioral observation techniques survey are the main technique that we used to do our survey and to collect data. The collected data being analyzed, compared and discussed in order to have a correct conclusion of " Sense of Place " on our studied area. These may include, among others, analyzing the character, continuity and enclosure, quality of the public realm, ease of movement, legibility, adaptability, and diversity by using suitable assessment methods.